การวิเคราะห์โครงข่ายด้วยระบบสารสนเทศภูมิศาสตร์เพื่อจัดการปัญหาการจัดเส้นทางสำหรับยานพาหนะในการขนส่งข้าวหอมมะลิ กรณีศึกษาจังหวัดร้อยเอ็ด - ไชยงาม, อภิษฎา; ไชยคราม, ธัญญรัตน์ (Thai Journal of Science and Technology, 2020)
This study is about the network analysis by using geographic information systems (GIS) to manage vehicle routing problem of the Jasmine rice transportation route from Petch Thung Kula Ronghai community enterprise in Roi Et province to multiple delivery districts. The objectives of this study are to study the transportation route of Jasmine rice from the enterprise group to the customer's location, and to analyze and suggest a suitable management vehicle route and cost reduction of shipping by using vehicle routing problem (VRP) in the condition of distance, expense, and weight of the goods. For the study of the transportation route of Jasmine rice from the enterprise group to the customer's location, there are 43 customers in 8 districts which are 16 customers in Muang district, 6 customers in each Kaset Wisai and Suvarnabhumi districts, 4 customers in Thawat Buri district, 3 customers in each Muang Suang, Chaturaphak Phiman, and At Samat districts and 2 customers in Changhan district. The result of the first objective shows that the community enterprise has to use 8 routes to deliver the Jasmine rice to customers which total distance is 675 kilometers and it also loses fuel 44.82 liters. Furthermore, the community enterprise spends money on transport cost of 954 baht in each delivery round. For the study of the analysis and suggestion for a suitable management vehicle route and cost reduction of shipping by using VRP in the condition of distance, expense, and weight of the product, it shows that VRP can reduce the number of delivered routes from 8 to 3 routes. This approach reduces the total distance from 675 to 413 kilometers and spends fuel only 17.29 liters. Moreover, the community enterprise spends money on transport costs only 586 baht which can minimize the transportation cost of 368 baht.